Effect of glass powder on the compression strength and the workability of concrete. Issue 1 (1st January 2017) - Rahma, Afif; El Naber, Nabil; Issa Ismail, Sherzad
Abstract: Several studies have been made to examine the potential mineralogical and mechanical properties of glass aiming to improve the characteristic properties of concrete where glass has been used in various forms, powder form or fine and coarse aggregate form, taken as part of aggregate or replacement of cement. However, the results presented in these studies were sometimes very different, even contradictory, due to the way in which the glass was used in these experiments, leading to a difficulty in distinguishing between the effect of Glass and the role of cement. To overcome this confusion the present research aimed to study the effects of glass powder on the properties of concrete by series of test for two constant quantities of cement, 350 and 400 kg per cubic meter. To reach the target of this research, two campaigns were done. In the first campaign the glass powder is gradually increased from trial to another by an increment of 2.5% of the cement's weight, from a rate of 2.5 up to 15%, without any chemical additive. This methodology made it possible to show the effect of the glass powder on the characteristic properties of concrete and defined its real contribution without being confused with the role of the cement. In the second campaign the study is extended to add the glass powder by rate of 7.5% to the batches with the use of super-plasticizer type F to investigate its potential mechanical properties. The slump test and compression test showed modest results in the first campaign but very important results in the second, when the glass powder was added with the plasticizer, which could be promoted to serve the concrete industry, particularly the production of the self compacting concrete where high performance concrete is required.